q-Analogues of the Bernoulli and Genocchi Polynomials and the Srivastava-Pinter Addition Theorems - Mahmudov, N. I. (Hindawi Ltd, 2012)
The main purpose of this paper is to introduce and investigate a new class of generalized Bernoulli and Genocchi polynomials based on the q-integers. The q-analogues of well-known formulas are derived. The q-analogue of the Srivastava-Pinter addition theorem is obtained.
Keywords: Euler Polynomials; Q-Extensions; Numbers